4(2x-1)-3(2x-3)=11-2(3-x)

Simple and best practice solution for 4(2x-1)-3(2x-3)=11-2(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)-3(2x-3)=11-2(3-x) equation:



4(2x-1)-3(2x-3)=11-2(3-x)
We move all terms to the left:
4(2x-1)-3(2x-3)-(11-2(3-x))=0
We add all the numbers together, and all the variables
4(2x-1)-3(2x-3)-(11-2(-1x+3))=0
We multiply parentheses
8x-6x-(11-2(-1x+3))-4+9=0
We calculate terms in parentheses: -(11-2(-1x+3)), so:
11-2(-1x+3)
determiningTheFunctionDomain -2(-1x+3)+11
We multiply parentheses
2x-6+11
We add all the numbers together, and all the variables
2x+5
Back to the equation:
-(2x+5)
We add all the numbers together, and all the variables
2x-(2x+5)+5=0
We get rid of parentheses
2x-2x-5+5=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| (22b-7)-7(3b+2)=-4 | | X2+6x+27=0 | | M+8=10m | | x/6+x/6=48 | | 200m-100m+48250=51000-150m | | 24÷4=3x | | 5+x*3=4*7+x | | 4x^2-x=-2 | | 3+6h=7+2h | | 4x=1+7 | | X+5/x-6=3/4 | | 2x+5/5=25 | | 12x-2=47+5x= | | -2*(3x-5)=x-25 | | (3x+18/7)+(x+32/5)=14 | | X+8+2x+8=40 | | x+3x/2=7/4 | | 4a/9=21 | | -2-6*4=x | | 33+7x=180 | | 4+1.1x=10.6 | | -4-(-8)=x | | 5x-4=12+2x | | 3x+18/7+x+32/5=14 | | (25^x)(16^x+10)=6400 | | 2y+-1=7 | | 20x-40=0 | | 274=153-v | | {5x+34=8x+94=12 | | 3x27/7+x+49/6=15 | | 2y=-9-1 | | 39=2v-3v-26 |

Equations solver categories